ANALISIS PEMAHAMAN MAHASISWA PGSD FKIP UNIVERSITAS RIAU TERHADAP PENDEKATAN SAINTIFIK PADA KURIKULUM 2013 - Eddy Noviana (Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The purpose of this research is knowing the understanding of PGSD FKIP University of Riau students about the scientific approach in the curriculum of 2013. Population in this research is students of PGSD FKIP University of Riau grade of 2013 with 137 students. The sample of this research is 36 students by using sample technique from Taro Yamane formula with 20% precision level. Data analysis technique used is descriptive statistical analysis technique. The results of this research indicate that: (a) in the one indicator of the legislation regulating the scientific approach obtained an average score is 6.67 with the category less; (b) the two indicators of understanding the scientific approach obtained an average score of 46.67 with the less category; (c) a three indicator of the requirements of a scientific approach, observing activity obtained an average score of 23.33 with less categories; (d) the fourth indicator of the scientific stage obtained an average score of 56.67 with sufficient category; (e), the five indicators of observation activity obtained an average score of 43.33 under the category of less; (f) the sixth indicator of the questioning activity obtained an average score of 51.67 with sufficient category; (g) the seven indicators of collecting information obtained an average score of 42.23 with the less category; (h) the eighth indicator of associate activity obtained an average score of 46.67 with the less category; And (i) on the nine indicator of communicating activity obtained an average score of 26.67 with less categories. Based on the data of the researchers, it can be concluded that the understanding of PGSD FKIP University of Riau students about the scientific approach in the curriculum of 2013 included in the category less with the average score 39,56. Abstrak Penelitian ini bertujuan untuk mengetahui pemahaman mahasisswa PGSD FKIP Universitas Riau terhadap pendekatan saintifik pada kurikulum 2013. Populasi dalam penelitian ini adalah mahasiswa PGSD FKIP Universitas Riau angkatan 2013 dengan jumlah 137 mahasiswa. Sampel penelitian ini berjumlah 36 mahasiswa dengan menggunakan teknik sampel dari rumus Taro Yamane dengan tingkat presisi 20%. Penelitian ini merupakan penelitian kuantitatif deskriptif. Hasil penelitian ini menunjukkan bahwa: (a) pada indikator satutentang peraturan perundang-undangan yang mengatur pendekatan saintifik perolehan rata-rata skor adalah 6,67 dengan kategori kurang; (b) indikator duatentang pengertian pendekatan saintifik memperoleh rata-rata skor sebesar 46,67 dengan kategori kurang; (c) indikator tigatentang persyaratan pendekatan saintifik, kegiatan mengamati memperoleh rata-rata skor sebesar 23,33 dengan kategori kurang; (d) indikator empat tentang tahap saintifik memperoleh rata-rata skor sebesar 56,67 dengan kategori cukup; (e), indikator limatentang kegiatan mengamati memperoleh rata-rata skor 43,33 dengan kategori kurang; (f) indikator enam tentang kegiatan menanya memperoleh rata-rata skor 51,67 dengan kategori cukup; (g) indikator tujuhtentang mengumpulkan informasi memperoleh rata-rata skor sebesar 42,23 dengan kategori kurang; (h) indikator delapan tentang kegiatan mengasosiasi memperoleh rata-rata skor sebesar 46,67 dengan kategori kurang; dan (i) pada indikator sembilantentang kegiatan mengkomunikasikan memperoleh rata-rata skor sebesar 26,67 dengan kategori kurang. Berdasarkan data hasil peneliti, maka dapat diusimpulkan bahwa pemahaman mahasiswa PGSD FKIP Universitas Riau terhadap pendekatan saintifik pada kurikulum 2013 termasuk pada kategori kurang dengan rata-rata skor 39, 56. Kata Kunci: Pemahaman, Pendekatan Saintifik, Kurikulum 2013